Pengaruh Pemberian Pupuk Organik Cair Batang Pisang Kepok (Musa paradisiaca L.) Terhadap Pertumbuhan dan Hasil Tanaman Sawi Samhong (Brassica juncea L.) - Janwardi Reywanda Tarigan; Nusyirwan (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2024)
This research aims to determine the effect of applying liquid organic fertilizer from Kepok banana stems on the growth and yield of Samhong mustard greens. The design used was a non-factual completely randomized design (CRD) with four treatments and six repetitions with doses of 0%, 10%, 20% and 30%. This research was carried out in the FMIPA greenhouse at Medan State University. The parameters tested were plant height, number of leaves, leaf area, wet weight and dry weight. The research results showed that the optimum dose of applying liquid organic fertilizer from Kepok banana stems to Samhong mustard greens was a concentration of 10%. Providing liquid organic fertilizer from kepok banana stems (Musa paradisiaca L.) had a significant effect on height growth, number of leaf blades, leaf area, wet weight and dry weight of Samhong mustard greens (Brassica juncea L.).